Biocatalysis for the production of pharmaceutical intermediates : statin precursors - Švarc, Anera (Array, 2019)
The application of enzymes in chemical synthesis, due to the recent advances, has a strong impact in multiple industries, especially the pharmaceutical industry. Namely, the use of enzymes shows remarkable advantages over classical chemical catalysis and therefore it is considered a ‘green’ solution. By using novel techniques, it is possible to tailor the enzymes to adapt them for a given process. Today, several pharmaceutical companies are successfully producing valuable precursors for the production of active pharmaceutical ingredients using enzymes, some of them being statin precursors. Statins are hypolipidemics, drugs used for the prevention of cardiovascular diseases and lowering cholesterol concentration in blood. Due to challenges in the chemical synthesis of statin intermediates, the production of statin intermediates using enzyme-catalysed reactions shows some notable advantages. Therefore, research and development laboratories, combined with reaction engineering techniques, have shifted their focus towards applying biochemical catalysis for the production of statin intermediates.